Aging quantification on alveolar bone loss - Sarajlić, Nermin, specijalist sudske medicine (Array, 2009)
Abstract: Objectives were to measure labial alveolar resorption using Lamendin’s method; to correlate the measured values of resorption with age at death; to determine whether age influences alveolar resorption, and if so, to quantify this impact. The study was performed during the 1992–1995 period in identified war casualties in Bosnia and Herzegovina. Data on the date, month and year of birth, and on the month and year of death were known in all cases. Measurements were carried out in 845 anterior monoradicular maxillary and mandibular teeth from male bodies (n=198) aged 23–69, divided into five age groups of 23–29, 30–39, 40–49, 50–59 and 60–69 years. Teeth with macroscopic pathologic lesions were excluded from analysis. Lamendin’s method was used to measure the alveolar bone level on the labial aspect of the extracted teeth. Results are presented in tables. Regression analysis was used to determine the alveolar resorption increase with age. Results are also presented by the factor of alveolar resorption, where the youngest age group was divided by older age groups. In the total sample of 845 teeth, alveolar bone level of up to 3.49 mm was recorded in 740 (87.76%), of 3.50–5.99 mm in 99 (11.79%), and of >6.00 mm in 6 (0.71%) teeth. In anterior monoradicular teeth, labial alveolar resorption increased with age and showed a regular age dependent pattern toward older age groups in mandibular but not in maxillary teeth. A >6-mm pocket was very rarely recorded. Study results contribute to clinical practice, demonstrating that periodontology is a preventive discipline in dental medicine